Assessments of CMIP3 Climate Models and Projected Climate Changes of Precipitation and Temperature for Vietnam and the Southeast Asia - Binh, Tran Nam (VNU Journal of Science: Earth and Environmental Sciences, 2020)
The main objective of this study is to assess the information of climate simulation and projection of temperature and precipitation based on the results of 23 models from the World Climate Research Programme’s (WCRP) Coupled Model Inter-comparison Project phase three (CMIP3) for Southeast Asian Countries with a more focus on Vietnam. The research is divided into two parts: i) Validation of the simulation of the 1948-2002 period with observations (gridded NCEP and CRU data and Vietnam’s surface station data) and ii) Assessments of projected climate changes for both precipitation and temperature variables. For the first part, depending on areas, main results showed a very systematic bias for the simulations of temperature and precipitation. CMIP3’s simulations have significant issues regarding high altitude regions, which can be explained by coarse of model resolutions to represent the effects of the complex topography, land-surface interactions, and the distorted albedo feedbacks due to extensive snow cover. In the second part, regarding the climate projection for  temperature, It is projected to get warmer from 3.5 to 6 degrees in 21 st Century in all scenarios. For the details in 2030 and 2050, the average annual temperature will clearly increase in the whole Vietnam. The trend of annual precipitation conditions at multi-scenarios in Southeast Asia compared to the current climate condition is not as clear as that of the temperature. The remarkable issue for Vietnam is in the A2 scenario, which provides the most change for the whole country.